Challenges and Opportunities for Madrasah in Improving The Competence of Graduate Students - Putra, Ali Musri Semjan; Siregar, Kardina Engelina (JURNAL AL-TANZIM, 2023)
This study aims to find out what madrasa strategies are in increasing the competence of graduate students in facing the globalization era at MAN 1 Pekanbaru and the factors that influence it. The informants in this study were school principals, curricula deputy heads, teachers and students of MAN 1 Pekanbaru. The madrasa strategy in increasing the competence of graduate students in facing the era of globalization at MAN 1 Pekanbaru is; 1) Changing the curriculum by adding material related to globalization; 2) Increasing the competence of teacher professionalism; 3) Changing the mindset of the teacher; 4) Improving the quality of madrasas; 5) Evaluate learning activities. Based on the results of observations, interviews, and documentation, it was found that the madrasah challenges were; 1) There is globalization; 2) Shifting educational paradigm; 3) Low public trust in madrasah productivity; 4) IT-based learning; 5) Curriculum changes; 6) Competence of madrasah graduates; 7) human resources produced by madrasas; 8) Network and collaboration of madrasah graduates.